The emulsifying performance of brewers' spent grains treated by colloid milling - Chin, Yi Ling; Dinani, Somayeh Taghian; Chen, Wei Ning; Boom, Remko (Innovative food science & emerging technologies, 2024)
The sustainable production of food ingredients can be achieved by utilising waste streams, but it is difficult to isolate pure components from a heterogeneous matrix. In this work, brewers' spent grains (BSG), which is a by-product from the brewing industry, was mildly treated with a colloid mill and its emulsifying ability was evaluated. The milled samples contained 26–32% protein and 52–62% fibre and were generally smaller than 10 μm. In its soluble fraction, a small amount of surface-active proteins was present and reduced oil-water interfacial tension by 35%. Emulsions prepared with the milled BSG and its insoluble particles were stable against coalescence for 10 days, with respective droplet sizes of 40 μm and 25 μm. The presence of fibres caused droplet flocculation but also helped to promote network formation. Our results suggest that obtaining pure components may not be necessary for emulsification purposes, especially for the case of particle-stabilised emulsions. Industrial by-products from food processing are generated in large quantities and typically discarded due to their recalcitrant nature. Yet, there is more that can be exploited from this waste stream including proteins and fibres. Separation of these components in their purified form would require harsh methods that are not environmentally sustainable. This study provided insights into the use of a mild and scalable process that can produce functionally active dispersions that are of interest in the preparation of emulsions.